A Study of Clinicoepidemiological Features and Association with Autoimmune Thyroiditis in Polymorphic Light Eruption - Mrudula Pulletikurti; KVT Gopal; PV Krishnam Raju; Rekha Rani Bulla (Clinical Dermatology Review)
Background: Polymorphic light eruption (PLE) is the most common idiopathic acquired photodermatosis. Previous studies have found an association between PLE and thyroid dysfunction. Objectives: The present study was conducted to study the clinicoepidemiological features and association with autoimmune thyroiditis in PLE. Materials and Methods: The study included 100 clinically diagnosed cases of PLE and 100 age- and sex-matched controls. In all patients, detailed history was taken regarding the skin eruptions, occupation, and symptoms of thyroid abnormality. Thorough clinical examination of skin lesions and thyroid gland was performed. Both cases and controls were subjected to thyroid function tests (TFTs) and patients with abnormal TFTs were further screened for thyroid autoantibodies. Results: The study included 61 females and 39 males with 20–40 years being the most common age group affected. Forearms, face, and neck were the most frequently affected body sites. A total of 45 cases and 9 controls showed abnormal thyroid profile (P = 0.0000), out of which thyroid autoantibodies were present in 18 cases and 3 controls (P = 0.0005). Ten out of 47 cases (21.2%) with primary episode of PLE and 35 out of 53 cases (66%) with recurrent PLE had abnormal TFT (P = 0.00001). Conclusion: All cases of PLE should be clinically examined for thyroid disorder and tested for TFT and thyroid autoantibodies in view of the significant association found between PLE and thyroid dysfunction. Prompt detection and treatment of thyroid dysfunction helps in preventing long-term morbidity and complications.